Perceived organizational support and moral distress among nurses - Navideh Robaee; Foroozan Atashzadeh-Shoorideh; Tahereh Ashktorab; Ahmadreza Baghestani; Maasoumeh Barkhordari-Sharifabad (BMC, 2018)
Abstract Background Moral distress is prevalent in the health care environment at different levels. Nurses in all roles and positions are exposed to ethically challenging conditions. Development of supportive climates in organizations may drive nurses towards coping moral distress and other related factors. This study aimed at determining the level of perceived organizational support and moral distress among nurses and investigating the relationship between the two variables. Methods This was a correlational-descriptive study. A total of 120 nurses were selected using random quota sampling method. A demographic questionnaire, Survey of Perceived Organizational Support, and Moral Distress Scale were used to collect the data which were analyzed using descriptive and analytical tests in SPSS20. Results The mean perceived organizational support was low (2.63 ± 0.79). The mean moral distress was 2.19 ± 0.58, which shows a high level of moral distress. Moreover, Statistical analysis showed no significant relationship between perceived organizational support and moral distress (r = 0.01, p = 0.86). Conclusion Given the low level of perceived organizational support and high moral distress among nurses in this study, it is necessary to provide a supportive environment in hospitals and to consider strategies for diminishing moral distress.